(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new deposit of gravels containing Pleistocene mammal remains mostly belonging to Hippopotamus sp., but also with remains of some other mammals (Elephas sp., Ursus sp.) has been located at Rocca Scodonì near Torrenova, in the province of Messina (Sicily). The new deposit may be compared with that of the S. Teodoro cave near Acquedolci, which was already known in the literature. The location, the elevation above present sea level, the facies and faunal association are closely similar. Like the deposit of the S. Teodoro cave, the deposit of Rocca Scodonì belongs to a coastal plain now elevated at the altitude of 60—130 m a.s.l., overlying an abrasion terrace which can be referred to the Eutyrrhenian cycle. The facies of deposits show that the morphological terrace which is now elevated at the altitude of 60—130 m a.s.l. and extends along Ionian and Tyrrhenian sides of North—Eastern Sicily, was built up with deposits of different ages and environments, which are connected to the interaction between Pleistocene uplift of the region and three marine transgressions. The size of skeletal elements of Hippopotamus sp. appears to be very near to that of the mainland species H. amphibius. The new deposit shows that other mammal remains can probablv be found in the future along the northern slopes of carbonate massifs present in the area of Rocca Scodonì—S. Teodoro cave.